Reduced expression of cyclooxygenase (COX) in idiopathic pulmonary fibrosis and sarcoidosis - Petkova, D K; Clelland, C A; Ronan, J E; Lewis, S; Knox, A J (Histopathology, 2003)
Aims:  To test the hypothesis that cyclooxygenase (COX)‐1 or COX‐2 expression is defective in lungs in idiopathic pulmonary fibrosis (IPF) and to characterize the cellular distribution. IPF is a progressive inflammatory lung disorder with an adverse prognosis. Previous work has shown that prostaglandin E2 (PGE2) regulates collagen deposition and fibroblast proliferation and a defect in COX regulation may contribute to the fibrosis that occurs in IPF. Methods:  Immunohistochemistry was utilized to determine COX immunoreactivity in lung sections from 25 IPF, six sarcoidosis and 14 control subjects. Results:  COX‐1 and COX‐2 expression in bronchiolar epithelial cells was significantly lower in IPF and sarcoidosis than in controls. No significant difference was found in COX‐2 expression between macrophages in IPF and control sections, but COX‐2 was reduced in macrophages in sarcoidosis compared with controls. Conclusions:  These studies confirm COX‐2 loss in bronchial epithelial cells but not macrophages in IPF, and show for the first time reduced constitutive COX‐1 expression in epithelial cells and macrophages. Similar abnormalities were observed in sarcoidosis.